EVALUATION OF MICROWAVE-ASSISTED EXTRACTION FOR ORGANOTIN DETERMINATION IN VEGETAL AND SOIL MATRICES - Bravo, Manuel A.; Parra, Sonnia; Verdugo C., Marcelo; Pérez V., Pablo; Quiroz, Waldo (Journal of the Chilean Chemical Society, 2017)
A new method for the extraction of methyl-, butyl-, phenyl- and octyltin compounds from soil and vegetal samples was proposed. The extraction procedure is based on an acidic solution in methanol for both matrices using a microwave system. The optimal conditions for each matrix were determined using the experimental design methodology and the respective figures of merit were evaluated. In optimal conditions, the analytes can be detected between 0.1-2.9 ng g-1 with repeatability lower than 6.5 % for both matrices. The extraction procedure was satisfactorily applied to spiked real samples, reaching recoveries ranged to 48.5-94.1% and 69-123 % for vegetal and soil samples, respectively. The proposed methodology is a promising alternative for control of organotin compounds in terrestrial ecosystems. Finally, the analytical performance of the proposed methodology was compared with published works in order to demonstrate its advantages and benefits.